2019
DOI: 10.1108/el-09-2018-0192
|View full text |Cite
|
Sign up to set email alerts
|

Image needs on social Q&A sites: a comparison of Zhihu and Baidu Zhidao

Abstract: Purpose This study aims to examine why users search for images, how users describe their image needs and what the images are used for by analysing questions obtained from two Chinese social Q&A sites, Zhihu and Baidu Zhidao. Design/methodology/approach A total of 1,402 image questions were collected from Zhihu and Baidu Zhidao. Both quantitative analysis and qualitative content analysis were performed to identify user image needs and the potential differences on the two social Q&A sites. Findings Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Zhihu is characterized by a large amount of knowledge sharing (Yang, 2023). Besides, Deng et al found that Zhihu users asked questions to promote subsequent discussion, whereas other platforms, such as Baidu Zhidao, often did so to seek information (Deng et al, 2019). Zhihu breaks the expert-sharing model of traditional knowledge platforms by allowing every user to share and receive knowledge (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhihu is characterized by a large amount of knowledge sharing (Yang, 2023). Besides, Deng et al found that Zhihu users asked questions to promote subsequent discussion, whereas other platforms, such as Baidu Zhidao, often did so to seek information (Deng et al, 2019). Zhihu breaks the expert-sharing model of traditional knowledge platforms by allowing every user to share and receive knowledge (Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Deng et al. found that Zhihu users asked questions to promote subsequent discussion, whereas other platforms, such as Baidu Zhidao, often did so to seek information (Deng et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Choi & Hsieh-Yee (2010);Deng et al (2019);Enser (2000);Enser et al (2007);Fry (1998);Goodrum (2005); Huang & Kelly (2013); Jörgensen et al (2014); Lee & Neal (; Enser et al (2007); Ercegovac (2012); Hastings (1999); Ménard (2011); Pu (2008) Technical Limitations 6 Göker et al (2016); Graham & Bailey (2006); Hastings (1999); Huang & Kelly (2013); Neal (2010); Yoon (2011) Issues of Aboutness 6 Fry (1998); Göker et al (2016); Huang & Kelly (2013); Hung (2005); Sedghi et al (2011); Yoon (. (2008); Given et al (2007); Göker et al(2016) …”
mentioning
confidence: 99%